Age-related anomalies of electrocardiograms in patients from areas with differential Seroprevalence of Chagas disease in Southern Bolivia. (May 2021) - Echalar, Jhean-Carla; Veliz, David; Urquizo, Omar N.; Niemeyer, Hermann M.; Pinto, Carlos F.
Abstract: Introduction: Chagas disease currently affects some 6 million people around the world. At the chronic stage, cardiomyopathy occurs in about 20–30% of infested people. Most prevalence studies have focused on young to adult people due to the drastic consequences of acquiring the pathogen and the possibility to cure the disease at this age; the prevalence of this disease, the effect of patients' sex and the consequences to senescent people have been largely neglected. This study looks to characterize the seroprevalence of Chagas disease and its relation with occurrence of electrocardiographic anomalies associated with sex and age, and to compare rural and urban populations in Bolivia. Methodology: Seroprevalence of Chagas disease was determined in blood samples and electrocardiograms were performed on seropositive individuals. Results: The rural population showed higher seroprevalence than the urban population (92% and 40%, respectively). The proportion of Chagasic cardiac anomalies in seropositive persons was highest in patients of the 50–59 age group (36%) as compared with the 40–49 (8%) and the ≥60 (17%) age groups. Conclusions: Higher seroprevalence in rural population was attributable to a higher probability to encounter the vector in rural areas. Increased exposure to infection and to development of the disease symptoms together with increased lethality of the disease as patients age explains the age-related Chagasic electrocardiographic anomalies. Since rural and urban populations showed different reactions under Chagas disease and the rural population was mainly of guaraní stock, the genetic and environmental determinants of the results should be further explored.